Regulating Switching Barriers in UK Retail Banking: the Student and Recent Graduate Market. - Garner, Philip M (2009)
The central objective of this research paper was to measure and analyse the impact of switching barriers in the UK retail banking industry. My analysis utilises a typographical framework developed by Burnham et al. (2003) in an attempt to ensure that my research not only furthers our understanding of the industry itself, but also of switching barriers in general.